¿Dónde está la mitología fenicia?: Al-Idrisi y los Aventureros de Lisboa (II) - Matesanz Gascón, Roberto (Gerión. Revista de Historia Antigua, 2005)
This work deals with the foregoings of story told by al-Idrisi, seen in the first part of this article. Specially, the form in which the myth could exists in the Iberian Peninsula, as soon as the relations between kabirim’s myth and social, economic and therapeutic practices, during Ancient Ages. Like reference point, is employed the story of Cambises expedition against the Ethiopians, narrated by Herodotus (III, 17-37).